Bioavailability, disposition kinetics and dosage of sulfadimethoxine in dogs--a correction. - Sams, R A (1977)
A reevaluation of the disposition kinetics and extent of absorption of sulfadimethoxine in normal dogs following intravenous and oral dosage has been made. The tissue to plasma level ratio at the peak tissue level (k12/k21) was 0.55, while the tissue to plasma level ratio after distribution equilibrium (k12/k21-beta) was 0.926. The systemic availability of sulfadimethoxine from the oral suspension was 48.8% (24.4-86.2) when corrections for intrasubject variability were made.